Survey on Multi-Objective Evolutionary Algorithms - Huang, Wenlan; Zhang, Yu; Li, Lan (Journal of physics. Conference series, 2019)
Multi-objective evolutionary algorithm (MOEA) is the main method to solve multi-objective optimization problem (MOP), which has become one of the hottest research areas of evolutionary computation. This paper surveys the development of MOEA and its research status, classifies it into four categories, analyzes the advantages and disadvantages of these algorithms, and summarizes the main application fields of MOEA. Finally several viewpoints for the future research of MOEA are presented.